SELECTED CONCEPTS OF DESIGN, IMPLEMENTATION AND DEVELOPMENT OF E-AGRITOURIST ACTIVITY IN PODLASKIE VOIVODESHIP - Stepaniuk, Krzysztof (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper contains a short analysis of two ways of Internet implementation as a tool of promotion of agritourist farms in Podlaskie Voivodeship. The analysis of Search Engine Results Pages (SERP) in 2009 and 2010 suggest that the short content about Agritourist farms within nationwide tourist portals was more efficient than individual websites. These portals have higher positions on Search Engine Result Page so the probability of finding specific farms was greater than in the case of individual websites of these farms.